Resveratrol Functionalized Carboxymethyl-β-Cyclodextrin: Synthesis, Characterization, and Photostability - Jin Gui Cheng; Bing Ren Tian; Qing Huang; Hu Rong Ge; Zhi Zhong Wang (Journal of Chemistry)
The resveratrol functionalized carboxymethyl-β-cyclodextrin conjugate was synthesized by two simple steps. The conjugate was successfully demonstrated by 1H NMR, 13C NMR, UV, and FTIR. The photostability of the conjugate was studied by ultraviolet absorption spectrum. After 360 min of UV light irradiation, the conjugate showed a total loss in absorbance of only 12.54%, while the resveratrol and its CM-β-CD inclusion complex showed a total loss in absorbance of 32.15% and 24.05%, respectively. The results indicate that the conjugate was more stable than resveratrol and its CM-β-CD inclusion complex.